2007
DOI: 10.1002/bit.21437
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of lipid hydrolytic activity by esterase on blotting membrane followed by separation using non‐denaturing two‐dimensional gel electrophoresis

Abstract: After separation by microscale non-denaturing two-dimensional gel electrophoresis (2DE) and transferring to a blotting membrane, major proteins are detected by a staining of direct blue 71 in a neutral solution. The carboxylesterase on the membrane hydrolyzes phosphatidylcholine after the spot of carboxylesterase is excised from the membrane, and incubated with phosphatidylcholine. Lipids of human serum proteins and the purified human high density lipoprotein (HDL) are removed by enzymatic hydrolysis when huma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2007
2007
2012
2012

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…However, it is difficult to recognize protein spots in the non-denaturing 2-DE gel when proteins are detected by reversible staining. Furthermore, we have reported that esterase is immobilized membranes without impairing its activity after extraction, separation, transblotting onto membranes and staining by a dye, direct blue [4]. However, it is difficult to recognize spots possessing enzyme activity on the membranes because the direct blue cannot be removed after staining.…”
Section: Introductionmentioning
confidence: 98%
“…However, it is difficult to recognize protein spots in the non-denaturing 2-DE gel when proteins are detected by reversible staining. Furthermore, we have reported that esterase is immobilized membranes without impairing its activity after extraction, separation, transblotting onto membranes and staining by a dye, direct blue [4]. However, it is difficult to recognize spots possessing enzyme activity on the membranes because the direct blue cannot be removed after staining.…”
Section: Introductionmentioning
confidence: 98%
“…So, in order to examine the continuous changes of substrates catalyzed by enzymes, it is preferable that enzymatic reactions are performed on the surface of a support without using chromophores. Since phosphatidylcholine and lipids of high density lipoprotein are hydrolyzed by an esterase on a polyvinylidene difluoride (PVDF) membrane after separation by non-denaturing 2-DE and electroblotting onto the membrane [8], retinoids such as retinylester, retinal, retinol and retinoic acid can be metabolized by enzymes on the membrane. It has been reported that abundant radical molecular ions [M +• ] of retinoids such as retinylester, retinal, retinol, and retinoic acid can be examined using laser desorption ionization time of flight mass spectrometry (LDI-TOF MS) [9,10].…”
Section: Introductionmentioning
confidence: 99%